The occupational attainment of American Jewry: 1990 to 2000 - Barry R. Chiswick (Institute for the Study of Labor (IZA), 2005)
This paper compares the occupational distributions in 1990 and 2000 of adult white men and women for American Jews and non-Jews, after adjusting for the changes in occupational classifications. The data are from the microdata files from the National Jewish Population Surveys (1990, 2000/01) and the 1990 and 2000 Censuses of Population. Among both men and women, American Jews had a greater proportion in the high level occupations (managerial and professional) in 1990, and the difference increased over the next decade. Among Jews and among non-Jews, there were only small gender differences in the proportions in the high level occupations. Thus, religion was more important than gender in explaining occupational patterns. American Jews of both genders experienced a continued decline in self-employment over the decade, and a continued shift among those in managerial and professional jobs away from self employment and toward being salaried workers.
Keywords: J15; J16; J22; Z1; 330; occupational attainment; Jews; religion; gender; National Jewish Population Survey